Topic Selection in Theme-Based Learning: EFL Students' Motivation and Reading Comprehension - Wilda; Oxtapianus Tawarik (International Journal of English and Applied Linguistics (IJEAL), 2026)
Reading comprehension and learning motivation remain persistent challenges for EFL students at the Senior High School level, particularly when assigned reading topics fail to connect with learners' personal interests and daily experiences. This study investigated the impact of topic selection in theme-based learning on the learning motivation and reading comprehension of Grade 10 students at SMAN 1 Anjongan, Mempawah Regency, West Kalimantan. A pre-experimental one-group pretest-posttest design was employed, with 32 students selected through purposive sampling. The independent variable was topic selection in theme-based reading instruction, operationalized through Generation Z-relevant topics including technology, social media, pop culture, and global current affairs. Learning motivation was measured using a 30-item questionnaire covering six dimensions based on Inocian et al. (2019), while reading comprehension was assessed through a 20-item multiple-choice test. Both instruments were validated through expert judgment, Pearson Product Moment correlation, and Cronbach's alpha reliability testing. Data were analyzed using Paired Samples t-test and Cohen's d. The results revealed statistically significant improvements in both learning motivation (t = 59.727, p = .000, d = 2.92) and reading comprehension (t = 54.647, p = .000, d = 2.40), with both effect sizes classified as huge according to Sawilowsky (2009). These findings confirmed that aligning reading topics with students' generational interests simultaneously enhanced motivational engagement and cognitive performance, providing empirical support for learner-centered, topic-relevant EFL reading instruction in rural Indonesian Senior High School settings.